The US Engagement in the Bilateral General Security of Information Agreement (GSOMIA) of Japan - South Korea As an Effort of Us Hegemony in the East Asia Region - Septiyanto, Defan Najmi; Poerwantika, Tine Ratna (Journal of Indonesian Social Sciences and Humanities, 2024)
North Korea's nuclear development is quite a serious problem for the East Asian region, especially Japan and South Korea, because nuclear development requires cooperation in the exchange of information or what is known as the general security of military information agreement (GSOMIA) between Japan and South Korea, but with the existence of factors Unfavorable history makes this cooperation difficult to agree on. The involvement of the United States in the East Asia region is considered as an affinity for both countries so that the two countries signed the GSOMIA cooperation. This research uses qualitative methods with the aim of finding out the complexity of the East Asian region, the United States' efforts to maintain its hegemony, and better understanding the content of GSOMIA bilateral cooperation. In this research, researchers used regional security complex theory, hegemony stability theory and the concept of security cooperation. This research explains how the development of North Korean nuclear activities ultimately makes conditions in the East Asia region increasingly complex. In this research, the author concludes that the United States' involvement in GSOMIA is an effort to maintain United States hegemony.